Passoando na pracinha: frevo livre instrumental multimodal - Altino, Maria José dos Santos (2025)
As part of the research line Processes and Dimensions of Artistic Production in Percussion, this dissertation presents the creation, interpretation, and analysis of a free instrumental frevo from a multimodal perspective. In this context, the work Passoando na Pracinha: frevo for percussion and dance in three movements — 1. Ferrolho, 2. Levada, and 3. Tramela — was composed, proposing a dialogue between tradition and modernity. It explores the creative freedom of free instrumental frevo while honoring its compositional tradition. The methodological approach involved performances in various academic and artistic contexts, audiovisual recordings of the presentations, and critical reflections on the different interpretations of each performance. The research was structured through a literature review, including both general and specific references relevant to the proposed focus, documentary research, audiovisual documentation of the experiments and performances, comparative analysis of the executions, and critical interpretation of the collected materials. Among the central elements of the investigation are the multiple possibilities for instrumental formation in the performances and the integration of dance as a constitutive part of the composition. The research also incorporates reflections by the author on her experiences as a woman in the context of instrumental frevo, highlighting the intersections between artistic creation, corporeality, and gender identity.